2011
DOI: 10.1037/a0024354
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning default effects: Why people choose not to choose.

Abstract: Default options exert an influence in areas as varied as retirement program design, organ donation policy, and consumer choice. Past research has offered potential reasons why no-action defaults matter: (a) effort, (b) implied endorsement, and (c) reference dependence. The first two of these explanations have been experimentally demonstrated, but the latter has received far less attention. In three experiments we produce default effects and demonstrate that reference dependence can play a major role in their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
190
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(195 citation statements)
references
References 32 publications
4
190
1
Order By: Relevance
“…When energy-inefficient ICBs were the default, they were chosen nearly 44 percent of the time. When the CFLB was the default, the ICB was chosen only 20.2 percent of the time (Dinner et al, 2011). The disparity is especially noteworthy in view of the fact that in the relevant experiments, people were not in the standard real-world situation of having to overcome inertia and to make a change.…”
Section: B Energy Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…When energy-inefficient ICBs were the default, they were chosen nearly 44 percent of the time. When the CFLB was the default, the ICB was chosen only 20.2 percent of the time (Dinner et al, 2011). The disparity is especially noteworthy in view of the fact that in the relevant experiments, people were not in the standard real-world situation of having to overcome inertia and to make a change.…”
Section: B Energy Efficiencymentioning
confidence: 99%
“…For example, the CFB would cost $11 in electricity per 10,000 hours, whereas the ILB would cost $49 per 10,000 hours. The CFB would cost $3 per bulb whereas the ICB would cost $0.50 per bulb (Dinner et al, 2011).…”
Section: B Energy Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown, however, that due to the inertia of decision makers, opting out is rather rare. This suggests that defaults or nudges might be an interesting way to promote widespread sustainable behavior (Dinner et al, 2011;Allcott and Mullainathan, 2010). A successful example related to purchasing energy-efficient and long-term economically profitable products is the furnishing of new buildings in the US with energy-saving light bulbs by default (Dinner et al, 2011).…”
Section: Inertia Social Network and Social Normsmentioning
confidence: 99%
“…Survey evidence on consumer demand for fuel economy in vehicles is consistent with loss aversion (Greene, Evans, and Hiestand 2013), while experimental research on energy use (Allcott 2011a;Goldstein, Cialdini, and Griskevicius 2008) lends support to the importance of reference points. For example, in three experiments, replacing incandescent light bulbs with more efficient CFLs as the default significantly increased the proportion of subjects who chose CFLs (Dinner et al 2011). Overall, however, little is known about the impacts of loss aversion and reference points on energy-efficiency investments, and more empirical research is needed to quantify their importance.…”
mentioning
confidence: 99%